Inflammatory Biomarkers and Sperm Dysfunction in ‎Bacterial Semen Infections - Samantaray, Satyanarayan; Jal , Soumya; Purohit, Gopal Krishna; Dash , Soumya (International Journal of Basic and Applied Sciences, 2025)
Male infertility is a global concern because bacterial infections of the reproductive tract play a ‎significant role. These infections trigger inflammatory responses that impair sperm quality. ‎This study explored the relationship between bacterial semen infection, inflammatory ‎biomarkers, and sperm dysfunction using PCR and quantitative real-time PCR (qPCR). ‎Semen samples were collected from 60 male participants attending the infertility clinics. ‎Semen analysis was performed according to the WHO 2021 guidelines to assess ‎concentration, motility, morphology, and viability. Bacterial DNA was isolated from the ‎samples and screened by PCR targeting 16S rRNA genes to detect common seminal ‎pathogens. The expression levels of inflammatory cytokine genes (IL-6, TNF-α, and IL-1β) ‎were quantified using SYBR Green-based qPCR. Gene expression was normalized to that of ‎GAPDH, which was used as a housekeeping gene. Correlations between bacterial presence, ‎cytokine expression, and sperm parameters were analyzed. PCR revealed bacterial DNA in ‎‎40% of the semen samples, with Escherichia coli and Staphylococcus aureus being ‎predominant. Samples positive for bacterial DNA showed significantly higher expression of ‎IL-6, TNF-α, and IL-1β (P < 0.01), indicating an inflammatory response. These elevated ‎cytokine levels correlated with decreased sperm motility, viability, and morphological ‎integrity (r > -0.6, p < 0.05). The study showed that bacterial infections in semen are ‎associated with the upregulation of inflammatory cytokines, contributing to sperm ‎dysfunction. PCR and qPCR effectively detect the presence of bacteria and quantify ‎inflammation at the molecular level. These findings underscore the need for molecular ‎diagnostics for male infertility evaluation and highlight inflammatory biomarkers as potential ‎therapeutic targets‎.
Keywords: Male Infertility; Semen Microbiota; Inflammatory Biomarkers; 16S rRNA; PCR; Cytokine ‎Gene Expression